Tetramerization of the S100B Chaperone Spawns a Ca2+ Independent Regulatory Surface that Enhances Anti-aggregation Activity and Client Specificity. Issue 19 (15th October 2022) - Figueira, António J.; Moreira, Guilherme G.; Saavedra, Joana; Cardoso, Isabel; Gomes, Cláudio M.
Graphical abstract: Highlights: S100B is a dimeric Ca 2+ protein known to inhibit Aβ42 and tau aggregation. Chaperone activity of S100B oligomeric forms secreted in the human brain is unknown. S100B tetramerization spawns a novel extended surface amenable to interactions with Aβ42. Tetrameric S100B has enhanced anti Aβ42 aggregation activity even in the apo state. Oligomerization fine-tunes activity and substrate specificity of the S100B chaperone. Abstract: Alzheimer's disease (AD) hallmarks include the aggregation of amyloid-β (Aβ), tau and neuroinflammation promoted by several alarmins. Among these is S100B, a small astrocytic homodimeric protein, upregulated in AD, whose multiple biological activities depend on localization, concentration, and assembly state. S100B was reported to inhibit the aggregation and toxicity of Aβ42 and tau similarly to a holdase-type chaperone. This activity is dependent of Ca 2+ -binding, which triggers the exposure of a regulatory binding cleft at the S100B dimer interface with which amyloidogenic clients dynamically interact. Although the dimer prevails, a significant portion of secreted S100B in the human brain occurs as higher order multimers, whose protective functions remain uncharacterized and which we here investigate. Resorting to ThT-monitored aggregation kinetics, we determined that unlike the dimer, tetrameric S100B inhibits Aβ42 aggregation at sub/equimolar ratios, an effect that persists in the absence of Ca 2+ binding. Structural analysis revealed that S100B tetramerization spawns a novel extended cleft accommodating an aggregation-prone surface that mediates interactions with monomeric Aβ client via hydrophobic interactions, as corroborated by Bis-ANS fluorescence and docking analysis. Correspondingly, at high ionic strength that reduces solvation and favours hydrophobic contacts, the inhibition of Aβ42 aggregation by tetrameric S100B is 3-fold increased. Interestingly, this extended Ca 2+ -independent surface favours Aβ42 as substrate, as tau K18 aggregation is not inhibited by the apo tetramer. Overall, results illustrate a mechanism through which oligomerization of the S100B chaperone fine-tunes anti-aggregation activity and client specificity, highlighting the potential functional relevance of S100B multimers in the regulation of AD proteotoxicity.